Antioxidant and antibacterial efficacy of Alyxia reinwardtii blume leaves and stems crude extracts - Kaly Sitthan, Vanishri (2021)
Medicinal plants contain phytochemical which play vital roles in determining the pharmacological properties existing in plants especially Alyxia reinwardtii Blume (Pulasari) which is a plant belong to family Apocynaceae. Phenolic compounds are parts of secondary metabolites mostly found in plant species with enormous structural diversities. The present study investigated the optimum extract yield, total phenolic and flavonoid content, antioxidant capacity and antibacterial activity in absolute methanol, hexane, acetone and distilled water of stems and leaves of Alyxia reinwardtii using Soxhlet extraction and cold maceration. The Folin-Ciocalteu reagent assay was used to estimate the phenolic content of extracts. The total flavonoid content was determined using aluminium chloride. The antioxidant capacity of the samples was evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical and Ferric Reducing Antioxidant Power (FRAP) assay. Antibacterial activity was investigated against Bacillus cereus and Escherichia coli using Disc Diffusion Assay (DDA), Minimum Inhibition Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Results showed that the methanolic extract on leaves using Soxhlet extraction showed highest crude yield (38.63 ± 1.72 %). Cold maceration on stems using acetone extract showed highest phenolic content (TPC) (170.44 ± 10.99 mg GAE/g) while hexane extract on leaves showed highest flavonoid content (TFC) (2957 ± 91.24 mg QE/g). Highest antioxidant activity was recorded with the methanolic extract using cold maceration extraction on leaves (75.81 ± 12.62 %) for the DPPH test and hexane extract (2278.89 ± 69.47 mg AAE/g) for the FRAP assay. For 50 % Inhibition Concentration (IC50) of DPPH radical, distilled water of leave extract showed the lowest value (1.69 ± 1.28 mg/mL) using Soxhlet extraction. Distilled water extract using Soxhlet extraction were potentially effective with variable efficiency against the tested bacterial strains with DDA (1.7 μg/mL), MIC (0.21 μg/mL) and MBC (0.85 μg/mL) on leaves. The results indicates that methanolic extract using Soxhlet extraction showed optimum crude yield meanwhile cold maceration is the most effective method for optimum antioxidant and antibacterial activity using the methanol and hexane, and distilled water extract respectively. Alyxia reinwardtii extract proved to be potentially effective as natural alternative for antioxidant and antibacterial due to its phytochemically potent for treating human diseases.